INOVASI CRACKERS DENGAN PENAMBAHAN BERAS HITAM DAN TEPUNG MOCAF SEBAGAI JAJANAN BERBASIS PANGAN LOKAL - Muhammad Umar Ridho; Ita Fatkhur Romadhoni; Any Sutiadiningsih; Qorry’ Aina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
High dependency on imported wheat flour drives the importance of healthy food diversification using local ingredients such as black rice and mocaf flour. This study aims to analyze the sensory characteristics and determine the best formulation of these composite crackers. The research used a quantitative experiment with a Completely Randomized Design (CRD) via organoleptic testing by 30 semi-trained and 3 trained panelists, analyzed using ANOVA at a 5% significance level. The results showed that formulation variations significantly affected texture and overall acceptance, but had no significant effect on color, aroma, and taste. Treatment 3 (21% black rice and 21% mocaf) was selected as the best formulation with the highest preference score of 1.92. This innovative product has great potential to be developed as an alternative functional healthy snack.